Crisis for Whom? Critical global perspectives on childhood, care, and migration - Rosen, Rachel; Chase, Elaine; Crafter, Sarah; Glockner, Valentina; Mitra, Sayani (UCL Press, 2023)
Children feature centrally in the ubiquitous narratives of 'migration crises'. They are often depicted as essentially vulnerable and in need of special protections, or suspiciously adult-like and a threat to national borders. At the same time, many voices, experiences, and stories are rarely heard, especially about children on the move within the global South. This bilingual book, written in English and Spanish, challenges simplistic narratives to enrich perspectives and understanding. Drawing on collaborations between young (im)migrants, researchers, artists and activists, this collection asks new questions about how crises are produced, mobility is controlled, and childhood is conceptualised. Answers to these questions have profound implications for resources, infrastructures, and relationships of care. Authors offer insights from diverse global contexts, painting a rich and insightful tapestry about childhood (im)mobility. They stress that children are more than recipients of care and that the crises they face are multiple and stratifying, with long historical roots. Readers are invited to understand migration as an act of concern and love, and to attend to how the solidarities between citizens and 'others', adults and children, and between children, are understood and forged.